Case studies in child, adolescent, and family treatment - LeCroy, Craig W.; Anthony, Elizabeth K. (Wiley, 2015)
"A detailed look at how to apply clinical theories to social work practiceThinking through real-life cases to make connections between theory and practice is a crucial element of social work education. Now in its Second Edition, Case Studies in Child, Adolescent, and Family Treatment contains a wide range of cases described in rich detail by practitioners, scholars, and researchers. Chapters represent contexts and approaches across the social work spectrum, so students will get to glimpse into the clinical experience of a full range of professionals.With chapter overviews, case sketches, study questions, and references for further study, this book makes an invaluable reference for social work students. Learning by example is the best way to develop the skill of clinical reasoning. Editors Craig W. LeCroy and Elizabeth K. Anthony--two distinguished scholars in the field of social work--have brought together an impressive roster of contributors who add their unique voices and clinical perspectives into their insightful case descriptions. Organized into five thematic sections, Case Studies in Child, Adolescent, and Family Treatment, Second Edition covers the most important areas in social work practice, including: Child welfare and adoption Individual and group treatment School and community settings Family treatment and parent training With the updates in the Second Edition, students will learn the most current lessons in social work practice from a diverse range of scholars, researchers, and practitioners in the field. In contexts ranging from child welfare to homelessness, this book provides the critical thinking skills students need to understand how social work theory applies in clinical environments"--Provided by publisher.